1984
DOI: 10.1177/000992288402300308
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation of Oral Anticoagulant Effect by L-thyroxine

Abstract: treatment of congenital dislocation of the knee. J Bone Joint Surg 1967;49-B:112-20. 4. Curtis BH, Fisher RL. Congenital hyperextension with anterior subluxation of the knee. J Bone Joint Surg 1969;51-A:255-69. 5. Laurence M. Genu recurvatum congenitum. J Bone Joint Surg 1967;49-B:121-34. 6. McFarlane AL. A report on four cases of congenital genu recurvatum occurring in one family. Br J Surg 1947;34:388-91. 7. Provenzano RW. Congenital dislocation of the knee. N Engl J Med 1947;236:360-2. 8. Chapple CC, David… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 9 publications
1
13
0
Order By: Relevance
“…The hypothesized warfarinlevothyroxine interaction described in these reports may be attributable instead to influences of the drug-disease state interaction and comorbidities, rather than an actual drug-drug interaction [11,13,[15][16][17][18]. Additionally, several of the case reports provide insufficient detail for adequate evaluation of potential causation [11][12][13][14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hypothesized warfarinlevothyroxine interaction described in these reports may be attributable instead to influences of the drug-disease state interaction and comorbidities, rather than an actual drug-drug interaction [11,13,[15][16][17][18]. Additionally, several of the case reports provide insufficient detail for adequate evaluation of potential causation [11][12][13][14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…Other mechanistic theories include levothyroxine-induced changes in the affinity of the warfarin target vitamin Kdependent epoxide reductase [22][23][24]. The conflicting evidence substantiating a warfarin-levothyroxine interaction contributes to the lack of consensus on the clinical significance and practice management of warfarin-receiving patients who start thyroid replacement therapy with levothyroxine [11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] The interaction between thyroid function and oral anticoagulation with warfarin has been well described, but no relationship between thyroid function and UFH has been documented in the literature. [9][10][11][12] Thyroid replacement (and/or hyperthyroidism) is associated with increased metabolism of vitamin K-dependent clotting factors, which in turn leads to an enhanced response to oral anticoagulation with warfarin. [9][10][11][12] I describe the case of a patient whose active hyperthyroid disease dramatically affected her UFH requirements.…”
mentioning
confidence: 99%
“…[9][10][11][12] Thyroid replacement (and/or hyperthyroidism) is associated with increased metabolism of vitamin K-dependent clotting factors, which in turn leads to an enhanced response to oral anticoagulation with warfarin. [9][10][11][12] I describe the case of a patient whose active hyperthyroid disease dramatically affected her UFH requirements. However, she exhibited a diminished anticoagulant response with UFH when in an actively hyperthyroid state.…”
mentioning
confidence: 99%
“…Although this potential interaction was first described in animal studies more than half a century ago, 28,29 case reports and small prospective studies have done little to expand our understanding of its frequency and clinical relevance. 19,[22][23][24][25][26][30][31][32][33][34] Increases in the international normalized ratio have been observed in clinical settings after patients receiving warfarin became thyrotoxic for various reasons, including after being given levothyroxine. 30 Similarly, small prospective studies observed increases in prothrombin time of up to 26 s in participants receiving warfarin when they were also given thyroid hormone.…”
Section: Introductionmentioning
confidence: 99%